Effect of Zoledronic Acid on Bone Mineral Density in Men with Prostate Cancer Receiving Gonadotropin-Releasing Hormone Analog. (29th July 2010) - Kapoor, Anoop; Gupta, Ankur; Desai, Nilay; Ahn, Hongshik
Abstract : Background . Loss of bone density with androgen deprivation therapy for prostate cancer is well recognized. We assessed the effects of quarterly infusion of zoledronic acid on bone mineral density (BMD) and markers of bone turnover over a one-year period in men receiving gonadotropin-releasing hormone analog (GnRH-a) for prostate cancer. Methods . 41 subjects were randomly assigned to treatment with zoledronic acid (4 mg) IV infusion or placebo every 3 months. The primary endpoint was the change in the lumbar spine BMD after 12 months of treatment. Results . The change in vertebral BMD in the zoledronic acid group (+ 7.93 ± 1.4 % ) was significantly (P < .05 ) greater than the change in the placebo group (+ 0.82 ± 1.7 % ) as was the change in left femoral neck BMD (+ 5.05 ± 1.4 % for the zoledronic acid group versus− 0.48 ± 1.4 % for the placebo group). The decrease in biochemical markers of bone turnover was significantly (P < .05 ) greater in the zoledronic acid group compared to the placebo group. Conclusion . Quarterly infusion of zoledronic acid for 1 year improved vertebral and left femoral neck BMD with a decrease in bone turnover markers in men on GnRH-a treatment. Zoledronic acid treatment appears to be promising in men with low BMD receiving GnRH-a treatment.